Grammarly as a Tool to Improve Students’ Writing Quality: Free Online-Proofreader across the Boundaries - Laksnoria Karyuatry (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2018)
This study aims at finding out whether the use of Grammarly could improve the students' writing quality related to writing descriptive. This study is conducted based on the lecturer's observation which implied that students had a problem with grammar and diction. From the interview, the lecturer said that the students felt bored and uninterested in writing. Moreover, most of the students thought that writing in English is so difficult. In order to overcome the problems, the researchers collaborated with the lecturer conducted an action research which involved 40 students. The research data were collected by three instruments, i.e. interview, students’ essays, and questionnaires. Then, the findings show that when Grammarly is used in teaching descriptive, there are 32 (82%) out of 40 students passed the passing grade. The researchers concluded that Grammarly can be used as an appropriate tool to minimize errors and improve students’ writing quality. Keywords: Writing quality; improvement; online-proofreader